PREPARATION OF FINANCIAL STATEMENTS FOR BUSINESS SUBJECTS - Nurmatov Zuhriddin Shavkat ugli; Masharipov Ozod Alimovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Accounting account international Standards 27 The purpose of the standard is to establish accounting and disclosure requirements for investments in subsidiaries, joint ventures and subsidiaries when an entity prepares separate financial statements. This Standard applies to accounting for investments in affiliates, joint ventures, and subsidiaries when an entity elects to present separate financial statements, or is required by national regulations to provide such reports.